Lease Accounting in Australia: Further Empirical Evidence - Hassan, Salleh; Christopher, Theo (Accounting Department,, 1998)
Key words: Australia; Accounting standard; Efï¬cient contracting; Lease accounting; Signalling The objective of this study is to examine the economic factors motivating Australian listed lessee ï¬rms to adopt capitalization of ï¬nance leases policy from 1985 to 1987 as permitted by the transitional provision of AAS 17. Capitalization is considered as the preferred accounting policy for ï¬nance leases compared to footnote disclosure. Adopting a joint efï¬cient contracting and quality signaling perspective, support for the research hypotheses would be construed as suggesting that capitalization is a means for lessee ï¬rms to reduce or mitigate agency and/or political costs and concurrently as a signal to the market that they are better quality ï¬rms. The sample consists of3l4 lessee ï¬rms; 67 ï¬rms as capitalizers and 247 ï¬rms as non-capitalizers. A pooled multivariate crossâ€”sectional analysis for 1985 to 1987 was performed incorporating sensitivity analysis to determine the â€œbestâ€ logistic regression model. This model was then assessed to determine its validity and predictive efï¬cacy. the results provide evidence that lessee ï¬rms adopted the capitalization as response to the media attention as being politically visible ï¬rms and concurrently as a signal to the market that they are better quality ï¬rms. The evidence also suggests limited usefulness of a lengthy transitional period.